Endoscopic treatment of ectopic teeth in the maxillary sinus - Masalha, Muhamed (J Clin Exp Dent, 2021)
BACKGROUND: Ectopic teeth in maxillary sinus is rare and are usually removed via sub-labial trans-canine fossa approach (SLCFA). The aim of our study was to present our experience with extraction of ectopic teeth in the maxillary sinus via transnasal endoscopic approach (TEA). MATERIAL AND METHODS: Rhinologists were asked to share their experience in the management of ectopic teeth in the maxillary sinus. Data were reviewed retrospectively. RESULTS: Eleven cases were reported in 10 patients from 2010 to 2019, six males and four females with a mean age of 33.5 +/-17 years (range 16 to 61). Seven patients complained of sinonasal symptoms, two were diagnosed incidentally during routine dental work-up, and one had oro-antral fistula. In eight patients, a cyst coexisted within the maxillary sinus. Teeth were located arbitrarily within the sinus. All cases were operated by TEA. One patient had self-limited periorbital emphysema, one had transient cheek numbness, and one had early post-operative bleeding that stopped after endoscopic cauterization. Long-term follow-up revealed good clinical outcomes. CONCLUSIONS: Transnasal endoscopic removal of ectopic teeth from the maxillary sinus is a feasible and rational approach when SLCFA is contraindicated. Key words:Ectopic teeth, dentigerous cyst, endoscopic sinus surgery, Caldwell-Luc.